Impact of 30 mL/kg fluid resuscitation completed within one hour on elderly septic shock patient - Tijun Gu; YePing Min; Lingling Zhang; Fang Jin; Fujing Liu (Annals of Medicine)
Objective This study aimed to investigate the prognostic impact of completing 30 mL/kg fluid resuscitation within 1 h in elderly septic shock patients.Methods This was a multicenter prospective observational cohort study. We applied logistic regression to assess the impact of completing 30 mL/kg fluid resuscitation within 1 h on respiratory support escalation including new-onset mechanical ventilation, bilevel positive airway pressure (BiPAP), and high-flow nasal cannula (HFNC) as well as heart failure (HF). We plotted Kaplan-Meier (K-M) curves to evaluate survival in patients completing 30 mL/kg fluid resuscitation within 1 h. We performed mediation analyses to determine the influence of HF on mortality associated with completing 30 mL/kg fluid resuscitation within 1 h.Results Completing 30 mL/kg fluid resuscitation within 1 h increased the odds ratios of new-onset BiPAP (adjusted OR = 3.411; 95% confidence interval (CI) = [1.526, 7.620]) and HFNC (adjusted OR = 2.576; 95% CI = [1.252, 5.297]) within 24 h as well as the odds ratio of HF (adjusted OR = 2.291; 95% CI = [1.266, 4.149]). The adjusted K-M curve showed that patients completing 30 mL/kg fluid resuscitation within 1 h had higher 30-d mortality than those completing it over longer periods. The mediation effect suggested that completing 30 mL/kg fluid resuscitation within 1 h could be fatal primarily because it increased the risk of HF.Conclusion For elderly patients with septic shock, completing 30 ml/kg of fluid resuscitation within 1 h ought to be more cautious, particularly considering the patient’s cardiac function and overall clinical status.